2020
DOI: 10.7150/jbji.40402
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Fungal Prosthetic Joint Infection

Abstract: Background: Fungal prosthetic joint infections (PJIs) are rare and often associated with poor outcome; however, risk factors are not well described. Methods: This was a retrospective case control study among all patients with PJIs from 2006-2016 at two major academic centers. Each fungal PJI case was matched 1:1 with a bacterial PJI control by joint (hip, knee, shoulder) and year of diagnosis. We compared demographics, comorbidities, and clinical characteristics between cases and controls using chi square/Fish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(45 citation statements)
references
References 29 publications
0
45
0
Order By: Relevance
“…Other species, such as C. glabrata and C. tropicalis, were more anecdotic (3–7% and 2–4%, respectively). Smaller series have found similar results [ 13 , 14 ], and in a recent review of the literature, C. albicans (47.3%) was the most frequent strain isolated, followed by C. parapsilosis (22.3%) [ 15 ], but epidemiology may still vary among regions.…”
Section: Epidemiologymentioning
confidence: 75%
See 1 more Smart Citation
“…Other species, such as C. glabrata and C. tropicalis, were more anecdotic (3–7% and 2–4%, respectively). Smaller series have found similar results [ 13 , 14 ], and in a recent review of the literature, C. albicans (47.3%) was the most frequent strain isolated, followed by C. parapsilosis (22.3%) [ 15 ], but epidemiology may still vary among regions.…”
Section: Epidemiologymentioning
confidence: 75%
“…(3) Immunosuppression secondary to malignant diseases, immunodeficiencies, or immunosuppressive therapy. Other risk factors reported in patients with CPJIs have been older age [ 18 ], diabetes, rheumatoid arthritis, malnutrition, and tuberculosis, which probably also reflect alterations in host immunity [ 2 , 12 , 13 , 14 , 23 ]. Other series have also identified that multiple previous surgeries at the site of the CPJI are also a risk factor [ 2 , 13 , 23 , 24 ].…”
Section: Pathogenesis and Risk Factorsmentioning
confidence: 99%
“…C. parapsilosis , C. tropicalis , and C. glabrata ) [ 9 ]. As reported in the literature, the incidence of C. albicans -mediated PJIs is around 1% [ 2 ].…”
Section: Discussionmentioning
confidence: 99%
“…The presence of a foreign body is the triggering event for infections, because it permits the attachment of microorganisms and biofilm formation, making the eradication of the infection difficult [ 1 ]. Gram-positive bacteria are the most common microorganisms implicated in PJIs, while infections mediated by fungi only account for 1% of cases in which Candida albicans is the leading organism [ 2 ]. When dealing with PJIs, a two-stage revision arthroplasty is widely used.…”
Section: Introductionmentioning
confidence: 99%
“…Patients who are immunocompromised, have an underlying systemic illness or have been subject to prolonged antibiotic regimens may have a higher risk of fungal infection. Prolonged wound drainage has also recently been identified as a potential risk factor[ 7 ]. The most likely cause of fungal infection in the reported case is the extensive use of antibiotics before identifying a definitve cause of the prosthetic joint infection.…”
Section: Discussionmentioning
confidence: 99%